2019
DOI: 10.1016/j.molcel.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hysteresis in CDK4/6 Activity Underlies Passage of the Restriction Point in G1

Abstract: Cells escape the need for mitogens at a restriction point several hours before entering S phase. The restriction point has been proposed to result from CDK4/6 initiating partial Rb phosphorylation to trigger a bistable switch whereby cyclin E-CDK2 and Rb mutually reinforce each other to induce Rb hyperphosphorylation. Here, using single-cell analysis, we unexpectedly found that cyclin E/A-CDK activity can only maintain Rb hyperphosphorylation starting at the onset of S phase and that CDK4/6 activity, but not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(144 citation statements)
references
References 44 publications
11
131
1
1
Order By: Relevance
“…We measured the response to a number of different types of stress signals and showed that most trigger first a rapid inactivation of CDK4/6 and that the loss in CDK4/6 activity is then followed by a reduction in CDK2 activity and exit to quiescence. This is also consistent with CDK2 activity and cell-cycle entry remaining sensitive to acute inhibition by the CDK4/6 inhibitor palbociclib until the end of G1 (Chung et al, 2019). We further show that CDK4/6 activity becoming increasingly more resistant to stress towards the end of G1.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We measured the response to a number of different types of stress signals and showed that most trigger first a rapid inactivation of CDK4/6 and that the loss in CDK4/6 activity is then followed by a reduction in CDK2 activity and exit to quiescence. This is also consistent with CDK2 activity and cell-cycle entry remaining sensitive to acute inhibition by the CDK4/6 inhibitor palbociclib until the end of G1 (Chung et al, 2019). We further show that CDK4/6 activity becoming increasingly more resistant to stress towards the end of G1.…”
Section: Discussionsupporting
confidence: 85%
“…Such a co-requirement for the two kinases has for example been proposed for Rb hyperphosphorylation (Zetterberg et al, 1995). Notably, a recent study by our group showed that CDK4/6 activity can still hyperphosphorylate Rb when all cyclin As and Es genes are missing in MEFs, suggesting that CDK4/6 activity alone can be sufficient for hyperphosphorylating the substrate Rb (Chung et al, 2019). We tested for a potential co-requirement of cyclin E/A-CDK2 activity in regulating the putative CDK4/6 reporter activity by also utilizing a Cre-Lox cell line to conditionally knockout all four cyclin E and A genes ( Figure 1 -supplementary figure 3A).…”
Section: Design and Validation Of A Fluorescent Reporter System To Momentioning
confidence: 60%
See 3 more Smart Citations